Algorithm to assess neutron HP(10) with estimation of uncertainties using Alnor albedo dosemeters: application in Brazilian nuclear power plants - Max da Silva Ferreira; Everton Rodrigues Silva; Cláudia Lúcia de Pinho Maurício (Brazilian Journal of Radiation Sciences)
The Instituto de Radioproteção e Dosimetria (IRD) is implementing an automatic neutron individual monitoring system, which uses albedo dosemeters from the Alnor manufacturer. For practical purposes, the occupational neutron fields have been divided into four application areas, named N1, N2, N3 and N4, as recommended in the German standard DIN 6802-4. For each area, specific Workplace Correction Factor (WCF), as a function of the ratio between photon dose responses measured in the incident and albedo component of the albedo dosemeter (Di/Da), must be used. This study proposes an algorithm for evaluating the photons and neutrons HP(10) values for the Alnor albedo system. It uses WCF × Di/Da curves previously defined by the authors, using MCNPX code simulations of the neutron dosemeter response for several occupational neutron fields. The methodology for calculating all uncertainties involved in the photon and neutron HP(10) assessment is also shown. Before the routine use of this system at IRD, several tests and calibrations are being carried out. This manuscript presents a case study carried out at the Angra I and Angra II power plants in 14 different fields (N1 application area). The results of the Alnor system are compared with those from the albedo system currently in routine use at the IRD. The average value of the ratio between the measurements with the Alnor system and the IRD system was 0.97 for photon HP(10), and 0.84 for neutron HP(10). Considering an expanded uncertainty to 95% confidence level, all results agree with each other.